THE ROLE OF THE WALI NAGARI SUNGAI KAMUNYANG IN RESOLUTING BULLYING BY TEENAGERS - Syahrani Rahma Putri; Muhammad Zulherawan (International Journal of Education and Social Science Studies, 2026)
This study addresses the limited scholarly attention to community-based governance mechanisms in resolving adolescent bullying, particularly within rural Indonesian contexts, which requires a resolution through the village government, particularly the Village Head as the village leader. Bullying among teenagers not only impacts the victims but also affects social relationships within the community. Therefore, an active role from the Village Head is needed to resolve this problem to create order and harmony within the community. This study aims to critically examine how village leadership operates as an informal social control mechanism in addressing adolescent bullying and to extend the application of social control theory in local governance contexts. This This study employs a qualitative case study design, using purposive sampling of eight key informants and thematic analysis to ensure analytical depth and rigor. Data collection techniques were conducted through interviews, observation, and documentation with eight informants: the Village Head, the Principal, the Chairperson of the National Child Protection Commission (KPAN), KPAN members, the perpetrator, the victim, the perpetrator's parents, and the victim's parents. The The findings reveal that the village head institutionalizes informal dispute resolution through mediation, moral guidance, and multi-stakeholder collaboration, thereby reinforcing social cohesion and behavioral regulation. These resolutions are conducted amicably with the goal of improving the perpetrator's behavior without damaging social relationships within the community. From a social control theory perspective, the village heads' resolutions demonstrate the strengthening of social bonds through supervision, value instillation, and community involvement, thereby preventing deviant behavior in adolescents. The study underscores the importance of integrating informal leadership structures into social control frameworks and offers practical insights for community-based bullying prevention strategies in similar socio-cultural settings. Therefore, collaboration between the village government, schools, parents, and the community is necessary in supervising and guiding adolescents